The Impact Of Work-Life Balance On Mental Well-Being Of Remote Working Generation Y Academicians Due To The Covid-19 Pandemic In Turkey - Yüceol, Nazlı; Urfa, Ayşe Merve; Sarp, Pınar; Binici, Ceylan Merve (My University, 2021)
The Covid-19 pandemic has profoundly affected labor markets and working styles. Within the scope of the precautions taken to ensure social isolation worldwide, remote working, one of the flexible working practices, has started to be used compulsorily in many sectors. With the transition to distance education in higher education, academicians have started to work remotely. Due to all these developments, the work and family life of the employees came together, and this situation brought many questions about worklife balance and mental well-being. The main objective of the paper is to determine the impact of remote working on mental well-being of generation Y academicians, due to the Covid-19 pandemic in Turkey. In this context, surveys were applied to 397 generation Y academicians working at public and private universities, and the relations were analyzed with the SPSS program. Based on the results, we confirmed the hypothesis that the work-life balance of the generation Y academicians who started working remotely due to the Covid-19 outbreak had a statistically significant positive effect on mental well-being. On the other hand, it was observed that the demographic characteristics and academic titles of the participants did not make a significant difference on work-life balance and mental well-being.

Covid-19 pandemisi, işgücü piyasalarını ve çalışma tarzlarını derinden etkilemiştir. Dünya genelinde sosyal izolasyonu sağlamak için alınan önlemler kapsamında esnek çalışma uygulamalarından biri olan uzaktan çalışma birçok sektörde zorunlu olarak kullanılmaya başlanmıştır. Yükseköğretimde uzaktan eğitime geçişle birlikte akademisyenler uzaktan çalışmaya başlamışlardır. Tüm bu gelişmeler nedeniyle çalışanların iş ve aile yaşamı bir araya gelmiş ve bu durum iş-yaşam dengesi ve mental iyi oluş ile ilgili pek çok soruyu beraberinde getirmiştir. Makalenin temel amacı, Türkiye’de Covid-19 salgını nedeniyle uzaktan çalışmanın Y kuşak akademisyenlerin mental iyi oluşları üzerindeki etkisini belirlemektir. Bu kapsamda kamu ve özel üniversitelerde görev yapan 397 Y kuşağı akademisyene anket uygulanmış ve ilişkiler SPSS programı ile analiz edilmiştir. Sonuçlardan yola çıkarak, Covid-19 salgını nedeniyle uzaktan çalışmaya başlayan Y kuşağı akademisyenlerin iş-yaşam dengesinin ruh sağlığı üzerinde istatistiksel olarak anlamlı bir olumlu etkisi olduğu hipotezi doğrulanmıştır. Öte yandan, katılımcıların demografik özelliklerinin ve akademik unvanlarının iş-yaşam dengesi ve ruh sağlığı üzerinde anlamlı bir fark yaratmadığı görülmüştür.
Türkiye’de Covid-19 Pandemisi Nedeniyle Uzaktan Çalışan Y Kuşağı Akademisyenlerin Mental İyi Oluş Halinin İş-Yaşam Dengesine Etkisi
Keywords: Covid-19 Pandemic; Generation Y; Mental Well-being; Remote Working; Work-Life Balance; D20; D23; Covid-19 Pandemisi; Y Kuşağı; Mental İyi Oluş; Uzaktan Çalışma; İş-Yaşam Dengesi